Is money going digital? An alternative perspective on the current hype - Daniel Gersten Reiss (Financial Innovation, 2018)
Current financial discourse suggests the imminence of a cashless society, a concept that arose from the global popularization of digital financial services and the development of technologies with the potential for application in financial markets. However, claims about the impending obsolescence of paper money are neither disruptive nor a novelty. Instead, this paper argues that the conversion of money from paper to bits has been a gradual, adaptive process, and that money is already digital. Moreover, in this paper we propose that the statuses of electronic money (e-money) and banknotes have switched in the view of monetary authorities.
Keywords: O3; L8; G21; E5; 650; Digital money; Digital currency; E-money; Digital financial services